A Study of Learning Achievement on Biomolecule Learning Unit Problems Solving Ability and Scientific Mind of Grade 10 Students Using Problem-Based Learning - Naowong, Jiraporn; Keeratichamroen, Wasana (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2019)
This research aimed to 1) compare learning achievement on Biomolecule learning unit of students, 2) compare problem solving ability, 3) compare scientific mind before and after learning unit and 4) compare learning achievement on Biomolecule learning unit of students using problem based learning between after learning and the 70 percent criterion. The sample group was grade 10 students in the second academic year of 2017 at Mattayomdankhontod School. There were 35 students and selected using cluster random sampling. The study tools were lesson plans with problem based learning, achievement test on Biomolecule learning unit, problem solving ability test and scientific mind questionnaires. The findings for this research were as follows: a comparison of learning achievement, problem solving ability and scientific mind before and after learning management was found that after learning was higher than before learning management at the .05 level, and after the learning achievement of learning unit on Biomolecule was higher than the 70 percent criterion with statistical significance at the .05 level.